Wood production and nutritional status of Pinus taeda L. in response to fertilization and liming: a meta-analysis of the Americas - Rodrigues VDS; Motta ACV; Barbosa JZ; Ercole TM; Prior SA (iForest - Biogeosciences and Forestry, 2023)
Loblolly pine (Pinus taeda L.) is one of the most planted forest species in the Americas. Since few studies have comprehensively assessed loblolly pine responses to fertilization, the present study performed a meta-analysis of the Americas based on 44 publications (1970-2022) of loblolly pine fertilization under field conditions. In general, fertilization increased root dry matter (+33%), litter (+21%), plant height (+6%), trunk diameter (+9%), wood yield (+30%), and needle concentrations of P (+9%), K (+36%), Ca (+17%), Mg (+14%), and S (+12%). Wood production was higher with residue fertilization, primarily with use of composite residues (cellulosic sludge + ash), compared to mineral fertilization. In regards to mineral applications, wood production was higher when multiple nutrients were added from fertilization and liming operations. Applications at planting (< 1 year) or on established trees (2-8 years), showed similar increases in wood production with higher responses occurring on sandy soils. These factors generally increased needle nutrient concentrations, except for no alteration or slight decreases in N under most conditions. The present study revealed loblolly pine responses to contrasting application strategies, which can help identify efficient fertility management practices for this commercially significant tree species.